The Impact of Brand Awareness, Perceived Quality, and Brand Associations on Female Consumers' Repurchase Intention in the Fashion Industry - Laksmana, I Nyoman Hendra; Sutedja, D.A Gladysia Sistadanta Kurnia Dewi (JUSTBEST Journal of Sustainable Business and Management, 2025)
The fashion industry in Indonesia, especially in Badung Regency, Bali, faces challenges in maintaining consumer loyalty amidst intense competition. One way to maintain loyalty is to understand the factors that influence consumer repurchase intention. This study aims to analyze the effect of brand awareness, perceived quality, and brand associations on repurchase intention in women who use fashion products. A quantitative approach was used with a descriptive correlational research design. Data were collected through questionnaires distributed to 96 respondents, and multiple regression analysis was conducted using SPSS. The results showed that all independent variables, namely brand awareness, perceived quality, and brand associations, had a positive and significant effect on repurchase intention. Among the three variables, perceived quality had the greatest influence. These findings indicate that fashion companies need to strengthen brand awareness, maintain product quality, and create positive brand associations to increase consumer loyalty and encourage repeat purchases. This study contributes to the development of consumer behavior and brand equity theories, as well as providing practical recommendations for companies in designing more effective marketing strategies.